Natural Products: Evidence for Neuroprotection to Be Exploited in Glaucoma - Adornetto, Annagrazia (Nutrients, 2020)
Glaucoma, a leading cause of irreversible blindness worldwide, is an optic neuropathy characterized by the progressive death of retinal ganglion cells (RGCs). Elevated intraocular pressure (IOP) is recognized as the main risk factor. Despite effective IOP-lowering therapies, the disease progresses in a significant number of patients. Therefore, alternative IOP-independent strategies aiming at halting or delaying RGC degeneration is the current therapeutic challenge for glaucoma management. Here, we review the literature on the neuroprotective activities, and the underlying mechanisms, of natural compounds and dietary supplements in experimental and clinical glaucoma.